Factors Affecting of the Inland Waterway Transport Volume Case Study Mekong River in Lao PDR - SAYNAVONG, Neevanh; PHETSANON, Touktik; SORXAYYVONG, Phoutsakhone; CHANTHANASINH, Vadsana; SENGCHANH, Souksamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The objectives of this research are an overview of the inland waterway transport volume along Mekong River in Lao PDR and the factors affecting of the inland waterway transport volume. Which use the data of Time Series Data from 1989 to 2019 that used modeling by Auto Regressive Distributed Lag (ARDL) in software Eviews 10 to analyze a long-term and a short-term relationship of variables. The results revealed that from 1989 to 2000, the volume of goods and passengers transported by water more than by land and air. The results of the ARDL model study showed that the long-term relationship of the number of water transport vehicles, ports, water level and number of logistic are relate in the same direction and moving together in the long run, which is in accordance with the set assumptions, while foreign direct investment is related in the opposite direction. The short run co-integration test shows that there are only three variables including the number of water transport vehicles, the average water level each year, and foreign funding, which has a short-term relationship with the volume of goods transported along Mekong River in Lao PDR with statistical significance levels of ten percent and five percent, respectively.